Pengembangan Kompetensi Sumber Daya Manusia Sektor Teknologi Informasi dan Komunikasi Papua Pegunungan - Teguh Priyantoro; Iki Tabo; Deisy Albert Ibrahim Yikwa (Universitas Methodist Indonesia, 2024)
The rapid development of information and communication technology (ICT) must be accompanied by the development of competent ICT sector human resources in accordance with Indonesian National Work Competence Standards (SKKNI). The developing Papua Highlands is expected to pay attention to the development of its human resources, primarily for the development of ICT sector human resource competencies. By qualitative method through rationalistic approach, the development is directed to competency type of computer operator. So with the achievement of these competencies, it will be easier to develop on the next types of competencies.